Association between gaseous air pollutants and idiopathic nephrotic syndrome in children: a 12-year population-based cohort study - Chieh Wang; Jeng-Dau Tsai; Lei Wan; Cheng-Li Lin; Chang-Ching Wei (BMC, 2022)
Abstract Background To date, there is insufficient knowledge about the association of air pollution and childhood nephrotic syndrome in the real world. This study aimed to evaluate the effects of the three common gaseous air pollutants, including sulfur dioxide, total hydrocarbon, and methane, on the risk of idiopathic nephrotic syndrome (INS) in children. Methods We collected data from the Taiwan National Health Insurance Research Database and Taiwan Air Quality-Monitoring Database. Children younger than 18 years old, identified from January 1, 2000, were followed up until the first diagnosis of INS was established or until December 31, 2012. We measured the incidence rates and hazard ratios for INS stratified based on the quartiles (Q1-Q4) of air pollutant concentration. Multivariate Cox proportional hazards models were also applied by adjusting age, sex, monthly income, and urbanization. Results Compared with participants exposed to Q1 concentrations, the adjusted hazard ratios (aHRs) for INS increased progressively along the four quartiles of sulfur dioxide, total hydrocarbon, and methane, from 1 (Q1) to 1.78 (Q4), 1 (Q1) to 3.49 (Q4), 1 (Q1) to 7.83 (Q4), respectively. Conclusions Our study revealed that children with exposure to higher concentrations of sulfur dioxide, total hydrocarbon, and methane was associated with an increased risk of INS.